A Fuzzy Analytic Hierarchy Process (FAHP) approaches for investment decision-making in Malaysia - Mohd Idris, Mohd Fazril Izhar; Abd Aziz, Khairu Azlan; Mhd Munawar, Ardini Athirah (UiTM Cawangan Perlis, 2025)
Investment decisions are essential for achieving financial growth and stability. Young Malaysians, however, often face challenges such as limited financial resources, rising living costs, and low financial literacy. Common investment options in Malaysia include gold, stocks, property, and cryptocurrency. Each option differs in capital requirements, profitability, risk level, and long-term viability. Selecting the most appropriate investment is difficult because decision making is often subjective and influenced by uncertainty. Conventional multi criteria decision making (MCDM) methods such as Simple Additive Weighting (SAW), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), and Analytic Hierarchy Process (AHP) have been widely used, but they are less effective in dealing with this challenge. To overcome this limitation, this study applies the Fuzzy Analytic Hierarchy Process (FAHP), which integrates fuzzy logic with AHP to capture expert evaluations more realistically. Four investment alternatives are assessed based on capital, profit, risk, and sustainability. The results indicate that gold is the most preferred investment option, followed by property, stocks, and cryptocurrency. By applying FAHP to investment decision-making in Malaysia, this study introduces a novel framework that not only supports young investors in making strategic choices but also offers insights that may inform financial literacy programs and policy initiatives under uncertain market conditions.